PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN JAS HUJAN MEREK PLEVIA DI TOKO DIAN DENPASAR - Juliansyah Eka Putra Nakrowi (Jurnal Bakti Saraswati (JBS), 2024)
The aim of this research is to understand the factors of consumer purchasing decisions. This research aims to determine the influence of brand image, product quality, and price perception on purchasing decisions for Plevia brand raincoats at Toko Dian Denpasar. This research was conducted at Toko Dian Denpasar. The collection method was through distributing questionnaires to 110 respondents who had purchased Plevia brand raincoats at Toko Dian Denpasar. The sampling technique used was purposive sampling. All data obtained from questionnaire distribution is suitable for use, then the collected data is tested and analyzed using multiple linear regression, hypothesis testing (t test and F test). The results of the analysis show that 1) Brand image has a positive and significant influence on the decision to purchase Plevia brand raincoats at Toko Dian Denpasar 2) Product quality has a positive and significant influence on the decision to purchase Plevia brand raincoats at Toko Dian Denpasar 3) Price perception has a positive and significant influence on the decision to purchase Plevia brand raincoats at Toko Dian Denpasar.